Material Selection of Machine Design using Expert System: A Comparative Study (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2023)
This research venture one of the major concerns in the field of expert system. Material selection an important key issue of machine design. Objectives of computerized selection procedure are reduced to personal bias and gives the more accurate optimized result. The concept of entropy; to evaluate the weight factor for each alternative material property or performance index, and the other is TOPSIS and SAW; to rank the candidate materials, for which several requirements are considered simultaneously. Sensitivity analysis is introduced here for better performance of selection.